HEALTHY FOOD, AN IMPORTANT FACTOR FOR THE WELFARE AND HUMAN’S HEALTH - Risto, Josif; Risto, Jora (European Scientific Journal, ESJ, 2015)
The eldest code for health and medicine, known as a primary health care, is described by OBSH in September 1978 as a form of the Declaration of Alma-ates. Among others, this declaration, with eight issues, orders in the first place how to provide healthy food, for all people without exception, especially for younger generations [7,8]. This rating shows the importance that OMS has given for the assurance of healthy food. The reason that today we have so many diseases related to food, does not apply only to the lack of food, but the surfeit of food produced from poisoned lands rich in pesticides which have disappeared necessary microorganisms, which enrich the soil with organic matters, necessary for the production of healthy food. A healthy soil produces healthy food, that builds a healthy body. How we nourish, foods that we use today and how to see our future in terms of providing a healthy food? These are some of our questions which have prompted us to undertake this study. Approximately 85% of persons have said that foods produced in a traditional way, are the most preferred of them, from food imported or produced in greenhouses. That are also expressed this way for the fresh foods compared to those stored in the refrigerator or preservatives.